2019
DOI: 10.1108/ijebr-03-2018-0174
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneuring as an everyday form of resistance

Abstract: Purpose The purpose of this paper is to problematise the dominant conceptualisation of entrepreneurship by recognising the everyday resistance inherent in mundane entrepreneurial practices. Its principle purpose is to show how entrepreneurial activities enacted by ordinary individuals in a marginalised and oppressed context can be an important means of resisting economic adversity, social marginalisation and political (colonial) domination. Design/methodology/approach Framed within de Certeau’s conceptualisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 85 publications
0
12
0
4
Order By: Relevance
“…Although it bears a resemblance to other countries in the Arab MENA region and throughout the world, occupied Palestine represents a peculiar case of 70 years of political struggle that continues to take its toll on Palestinians. Velloso (1996) suggested that Palestinian women are faced with three interweaving layers of structural complexity-signaling the metanarratives of patriarchy, religion, and politics-that largely shape their opportunities, choices, and entire life situations both at home and at work (Granerud 2012;Sabella and El-Far 2019;Sultan 2016).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it bears a resemblance to other countries in the Arab MENA region and throughout the world, occupied Palestine represents a peculiar case of 70 years of political struggle that continues to take its toll on Palestinians. Velloso (1996) suggested that Palestinian women are faced with three interweaving layers of structural complexity-signaling the metanarratives of patriarchy, religion, and politics-that largely shape their opportunities, choices, and entire life situations both at home and at work (Granerud 2012;Sabella and El-Far 2019;Sultan 2016).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…First, in contrast to Ramsay and Letherby's (2006) specific concern with the experiences of academic non-mothers, this study explores the narratives of both mothers and non-mothers and demonstrates how the institutionalized practices found within both the university and household spheres shape women academics' experiences, irrespective of their social status. Second, by investigating the experiences of academic mothers and non-mothers embedded within the Palestinian context, this study adds to the very limited body of literature on women academics working in turbulent and marginalized societies, especially those defined by colonialism, oppression, patriarchy, and conservatism-like occupied Palestine-who have to deal with the additional constraints associated with a prolonged colonial occupation and the resultant socio-economic disadvantages (Granerud 2012;Rought-Brooks et al 2010;Sabella and El-Far 2019). Finally, and in spite of the formidable evidence substantiating the deterring effect of motherhood and the household upon women academics' career progression (Raddon 2002;Ramsay and Letherby 2006;Wolf-Wendel and Ward 2006), this study attempts to explore unorthodox interpretations of the notion of motherhood and its influence.…”
mentioning
confidence: 99%
“…To maintain gender conformity, the role of husbands is not only considered natural, but also expected in that society (Constantinidis et al, 2019). In the old city of Jerusalem, although traditionally Palestinian women are not expected to be exposed to the outside world, husbands are found to help them in street vending while the family is struggling with socio-political and economic challenges (Sabella & El-Far, 2019). Additionally, many men encourage their wives to engage in entrepreneurship in Pakistan to support the economic development of the country (Lindvert et al, 2017).…”
Section: The Role Of Husbandsmentioning
confidence: 99%
“…Se encuentran aquí investigaciones sobre el trabajo en equipo (van den Broek et al, 2008), voluntario (O'Toole & Grey, 2016) y no remunerado (Baines, 2004). De la misma forma, incluyen investigaciones sobre el papel emancipatorio de ciertas formas de emprendimiento Estudios Organizacionales (Sabella & El-Far, 2019) y sobre el potencial del liderazgo para movilizar la resistencia colectiva en el lugar del trabajo (Zoller & Fairhurst, 2007).…”
Section: Formas Mecanismos O Estrategias De Resistenciaunclassified